Overview and specifications of laser and target areas at the Intense Laser Irradiation Laboratory. (22nd February 2021) - Gizzi, Leonida A.; Labate, Luca; Baffigi, Federica; Brandi, Fernando; Bussolino, Giancarlo; Fulgentini, Lorenzo; Köster, Petra; Palla, Daniele
Abstract: We present the main features of the ultrashort, high-intensity laser installation at the Intense Laser Irradiation Laboratory (ILIL) including laser, beam transport and target area specifications. The laboratory was designed to host laser–target interaction experiments of more than 220 TW peak power, in flexible focusing configurations, with ultrarelativistic intensity on the target. Specifications have been established via dedicated optical diagnostic assemblies and commissioning interaction experiments. In this paper we give a summary of laser specifications available to users, including spatial, spectral and temporal contrast features. The layout of the experimental target areas is presented, with attention to the available configurations of laser focusing geometries and diagnostics. Finally, we discuss radiation protection measures and mechanical stability of the laser focal spot on the target.